Photo Preparation (Raton, NM Raton Range, 1984)
Article is about an early camera obscura to be exhibited.
Newspaper article + Photograph of Candace Mathews and Tom Burch "Natural Magic - From the Cradle to the Grave"
Master list item #: 92
File location is in the Raton file Cabinet
Keywords: Mathews, Candace; Burch, Thomas (Tom); Raton Museum; Photographic History; Museum Exhibits; Museum Displays; Easter Receptions; Local History; Coors Building; Historic 1st Street; Raton, New Mexico